The use of chemometrics analysis as a cost-effective tool in sustainable utilisation of water resources in the Langat River catchment - Juahir, H.; Jan, I.K.M.; Jalaludin, A.; Mokhtar, M.B.; Zain, Sharifuddin Md; Ekhwan, T.M. (2008)
Malaysia was adopted the concept of sustainable development as mentioned in the National Documents of the 8 Malaysian Plan and OPP3. This calls for environmental studies within the context of the sustainable science and governance. This study details the application of chemometrics in environmental chemistry for sustainable utilization of resources in the Langat Basin, Selangor, Malaysia. We hope to demonstrate in this work the importance of historical data, if they are available, in planning sampling strategies to achieve desired research objectives. To achieve the objectives, this study highlights the possibility of determining the optimum number of sampling stations, which in turn would reduce cost and time of sampling. The seasonally dependent water quality data of Langat River was investigated during the period of December 2001 to May 2002. Monthly water samples were collected from four different stations. Concentrations of nitrate, sulfate, phosphate, lead, cadmium, iron, zinc and copper were determined. Dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), temperature, pH, total suspended solids (TSS), ammoniacal nitrogen (AN) and conductivity were measured insitu. Chemometric treatments using cluster, principal component analysis and factorial design were employed where data were characterized as function of season and sampling sites, thus, enabling significant discriminating factors to be discovered. Results showed that at a chord distance of 75.25 the cluster gave two groups of sampling plot. Group I consists of 6 sampling stations while Group II consists of 14 sampling stations. The two clusters are discussed in terms of the difference in data variability.